The Influence of Earnings Quality and Dividend Policy on Company Value - Putu Dina Cristina; Gerianta Wirawan Yasa (International Journal of Management Research and Economics, 2024)
Company value is an important aspect that needs to be considered It highlights the company's performance, which can shape investors' perceptions of the business. The aim of the research is to provide empirical evidence regarding the influence of earnings quality and dividend policy on company value. Company size and leverage are used as control variables in this research. The research uses PBV as a proxy for company value, DACC as a proxy for earnings quality, DPR as a proxy for dividend policy, total assets as a proxy for company size and DER as a proxy for leverage. This research was conducted on companies listed on the Indonesia Stock Exchange (BEI) in 2012-2022. The number of samples taken was 6325 observation samples using the non-probability sampling method, especially using the sampling technique, namely purposive sampling. Data collection was carried out using non-participant observation. The analysis technique used is multiple linear regression analysis technique. The results of this research indicate that earnings quality has no effect on company value and dividend policy has a positive effect on company value.